Design Approaches and Achievements of Novel Wrought TiAl Alloys for Jet Engine Applications. (12th February 2019) - Wakabayashi, Hideki; Signori, Loris J.; Shaaban, Ali; Yamagata, Ryosuke; Nakashima, Hirotoyo; Takeyama, Masao
Abstract: Design approaches and achievements for the development of wrought TiAl alloys to be used for LPT and HPC blades are constructed. In case of Ti-Al-M1 -M2 quaternary systems, conventional equivalency concept does not work for the alloy design, and a new thermodynamic database for phase diagram calculations in multi-component systems of the alloys is built by introducing the interaction parameters among four phases of β−Ti, α2 −Ti3 Al, α−Ti and γ−TiAl phases in the systems, in order to reproduce the experimentally determined phase diagrams. Based on the phase diagram calculations, the composition range of a unique phase transformation pathway of β+α→α→β+γ in the multi-component system can be identified, and thus model alloys with excellent hot workability even at higher strain rate and mechanical properties can be successfully proposed. It can be concluded that an introduction of bcc β phase and the morphology control through the phase transformation pathway make it possible to improve the room temperature ductility, creep and fatigue crack propagation resistance.